Measuring the efficiency of Polish banks using stochastic frontier approach - Skrzypek, Jurand; Trojak, Mariusz Radosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
The aim of the paper was to estimate the level of efficiency of commercial banks operating in Poland. In order to do that, authors evaluated the level of development of the polish banking system and with the use of the parametric Stochastic Frontier Approach (SFA) the average inefficiency was estimated (for 34 banks between 2005 and 2011). The intermediation approach was applied to determine the inputs and outputs of banks. In the analyzed period the average efficiency level was increasing. Significant impact on technical efficiency had the financial crisis. Home field advantage hypothesis  and global advantage hypothesis were also verified. The crisis decreased efficiency. The work has the following structure: in the first part the characteristics of the polish banking system were presented. In the second part the authors showed the results of the most important works on efficiency for Polish banking sector, than the research method, data and results were presented. In the last part the most important conclusions were pointed out.